2001
DOI: 10.1074/jbc.m102902200
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sulfur Cluster Assembly

Abstract: The synthesis of iron-sulfur clusters in Escherichia coli is believed to require a complex protein machinery encoded by the isc (iron-sulfur cluster) operon. The product of one member of this operon, IscA, has been overexpressed, purified, and characterized. It can assemble an air-sensitive [2Fe-2S] cluster as shown by UVvisible and resonance Raman spectroscopy. The metal form but not the apoform of IscA binds ferredoxin, another member of the isc operon, selectively, allowing transfer of iron and sulfide from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
97
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(103 citation statements)
references
References 29 publications
5
97
1
Order By: Relevance
“…coli contains both the ISC and SUF systems (2)(3)(4) clusters and transfer them to apoproteins (14)(15)(16)(17)(18). Three conserved Cys residues could act as ligands for these clusters, as indicated by mutagenesis studies and by the recently obtained 3D structure of IscA (26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…coli contains both the ISC and SUF systems (2)(3)(4) clusters and transfer them to apoproteins (14)(15)(16)(17)(18). Three conserved Cys residues could act as ligands for these clusters, as indicated by mutagenesis studies and by the recently obtained 3D structure of IscA (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Cysteine desulfurases provide sulfur from Lcysteine (11). Scaffolds are defined as being able to bind both iron and sulfur so that a Fe-S cluster can form before being transferred to targeted apoproteins (12)(13)(14)(15)(16)(17)(18). The SUF system includes an atypical cytosolic ABC-type transporter that functions with the cysteine desulfurase for increasing the production of sulfur (19,20).…”
mentioning
confidence: 99%
“…Genetic and biochemical studies have shown that two gene products, NifS and NifU, are essential for assembly of the Fe-S clusters in nitrogenase (3)(4)(5)(6). Subsequent studies in a wide variety of prokaryotes resulted in the identification of the isc (iron-sulfur cluster assembly) operon (7,8), which encodes the translational regulator IscR (9), cysteine desulfurase IscS (7), scaffold proteins IscU (10) and IscA (11,12), chaperone proteins HscA and HscB (13), and ferredoxin Fdx. IscS is a cysteine desulfurase that generates alanine and elemental sulfur by means of the formation of a persulfide intermediate on a cysteine residue (4,14).…”
mentioning
confidence: 99%
“…A conserved cysteine residue on IscU accepts sulfur from IscS during Fe-S cluster building (10 -12). IscA also can form Fe-S clusters and may function as an alternate scaffold (13,14). Downstream of the isc operon is the hscB-hscA-fdx operon.…”
mentioning
confidence: 99%